Blow molding grade hydrogen storage tank liner material and preparation method thereof

By adopting PA resin, toughen mother grains, and other high -performance ingredients in the inner duality material of hydrogen storage tanks, the problem of decreased hydrogen permeability of existing materials under high -pressure conditions has been solved, and better hydrogen block effects and low temperature effects are achieved. Toughness meets the safety storage requirements of new standards.

CN119371814APending Publication Date: 2025-01-28NANJING JULONG SCIENCE & TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411325045.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing hydrogen storage tank inner material has reduced hydrogen permeability under high pressure conditions, resulting in bubble phenomenon and cannot meet the new standard GB/T 42610's requirements for the storage safety of hydrogen storage tanks.

Method used

A kind of brunting material of the hydrogen storage tank is used, including PA resin, toughenal, ethylene alcohol cluster, inorganic fillers, chain expansion agents, lubricants, and antioxidants. The co -mixed with PA resin is made of toughened maternal particles, and the hydrogen resistance and low temperature toughness of the material are improved.

Benefits of technology

It significantly improves the hydrogen resistance and low temperature toughness of the hydrogen storage tank's inner linery material, avoids the emergence of bubble phenomena, and meets the safety storage requirements of hydrogen storage tanks under high pressure and low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005055180270000081
    Figure BDA0005055180270000081
  • Figure BDA0005055180270000091
    Figure BDA0005055180270000091
  • Figure BDA0005055180270000092
    Figure BDA0005055180270000092
Patent Text Reader

Abstract

The invention provides a blow molding grade hydrogen storage tank liner material and a preparation method thereof, and relates to the technical field of high polymer material modification. The material comprises the following components in percentage by weight: 48-78% of PA resin; 20 to 50 percent of toughening master batch; 0.5-3% of an ethylene vinyl alcohol copolymer; 0.5-3% of an inorganic filler; 0.1%-1% of a chain extender; 0.4 to 0.8 percent of lubricating agent; 0.2 to 0.5 percent of an antioxidant; during preparation, the maleic anhydride copolymer and the PA resin are prepared into the toughening master batch, then the PA resin, the toughening master batch, the ethylene-vinyl alcohol copolymer, the inorganic filler, the lubricant and the antioxidant are mixed to prepare a PA composite material semi-finished product, and finally the PA composite material semi-finished product and the chain extender are mixed to prepare the blow molding grade hydrogen storage tank liner material. The PA resin material with better hydrogen barrier property is matched with the high-barrier component to improve the hydrogen permeability of the nylon material, and the viscosity of the PA composite material is improved through tackifying of the chain extender and preparation of the toughening master batch, so that the hydrogen storage tank liner is formed by adopting a blow molding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material modification, and in particular to a blow molding-grade hydrogen storage tank liner material and a preparation method thereof. Background Art

[0002] The selection of hydrogen tank liner materials is directly related to the safety and pressure resistance of the hydrogen tank. Pressure resistance is to ensure that the hydrogen tank can withstand high-pressure environments and ensure the safe storage and transportation of hydrogen. Under high-pressure environments, the liner material needs to be able to withstand a certain pressure without cracking or deforming, thereby ensuring the normal operation of the hydrogen tank. The pressure resistance requirement of the liner material is one of the important considerations in the design of hydrogen storage tanks. The current hydrogen tank liner materials are mostly high-density polyethylene (HDPE) and nylon PA6. Among them, HDPE has higher hydrogen permeability than PA6 and is generally used for hydrogen storage bottle liners with lower pressures. For hydrogen storage bottle liners with pressures greater than 70mpa, PA6 materials are mostly used.

[0003] For example, the prior art patent application CN117624879A proposes a composition for a gas tank liner, wherein the composition is obtained by hot-melt kneading raw materials containing at least i. polyamide; ii. halogenated isobutylene rubber, and iii. a rubber compounding agent; the composition is prepared by mixing halogenated isobutylene rubber with polyamide, and the halogenated isobutylene rubber is dynamically vulcanized during the mixing and hot-melt kneading process, so that the formed composite material has excellent impact resistance and hydrogen permeability resistance, and is suitable for use as a raw material for a gas tank liner. For another example, patent application CN110511560A discloses a polyamide resin composition for hydrogen storage containers or hydrogen piping, which composition contains 100 parts by weight of (A) polyamide resin, 0.01-6 parts by weight of (B) a particulate inorganic compound, and 0.01-12 parts by weight of (C) an organic compound having three or more hydroxyl groups or three or more amino groups in one molecule and a number average molecular weight (Mn) of less than 2000. The composition has excellent hydrogen barrier properties and can be used in hydrogen storage containers or hydrogen piping.

[0004] However, with the development of the economy, the new standard GB / T 42610-2023 has further improved the storage safety requirements for hydrogen storage tanks; the polyamide modified materials disclosed in the prior art can no longer meet the target high-pressure requirements of hydrogen storage tanks; under high-pressure conditions, the hydrogen permeability resistance of the existing PA6 modified materials decreases, resulting in the occurrence of bubbling. It is necessary to develop new materials that can meet the standard requirements of hydrogen storage tanks to adapt to social development. Summary of the invention

[0005] The object of the present invention is to provide a blow molding grade hydrogen storage tank liner material and a preparation method thereof, which increases the viscosity of the resin by thickening and preparing a toughening masterbatch, and improves the hydrogen permeability of the nylon material by adding a high barrier component, so that not only the nylon material can be blow molded, but also the low-temperature toughness of the hydrogen storage tank liner material is ensured.

[0006] To achieve the above object, the present invention proposes the following technical solutions:

[0007] In the first aspect, a blow molding grade hydrogen storage tank liner material is proposed, characterized in that it includes the following components in weight percentage: PA resin, 48-78%; toughening masterbatch, 20-50%; ethylene vinyl alcohol copolymer, 0.5-3%; inorganic filler, 0.5-3%; chain extender, 0.1-1%; lubricant, 0.4-0.8%; antioxidant, 0.2-0.5%.

[0008] Furthermore, the toughening masterbatch is prepared by blending a maleic anhydride graft copolymer with a PA resin, wherein the mass percentage of the maleic anhydride graft copolymer is 45-50%.

[0009] Furthermore, the PA resin is selected from one or more of PA6, PA610, PA612, PA11, PA12, PA1010, PA1012 and PA1212.

[0010] Furthermore, the relative viscosity of the PA resin is not less than 2.5.

[0011] Furthermore, the inorganic filler is a lamellar inorganic filler, and the lamellar inorganic filler is a combination of one or more of mica, wollastonite and montmorillonite.

[0012] Furthermore, the maleic anhydride grafted copolymer is at least one of maleic anhydride grafted POE, maleic anhydride grafted EPDM, and maleic anhydride grafted PE.

[0013] Furthermore, the amount of the chain extender does not exceed 2.5% of the total weight of the PA resin in the blow molding grade hydrogen storage tank liner material, and the chain extender is a linear molecular chain extender containing polycarbonate functional groups with a molecular weight less than 20,000.

[0014] Furthermore, the chain extender is a linear molecular chain extender containing a polycarbonate functional group.

[0015] In the second aspect, a method for preparing a blow molding grade hydrogen storage tank liner material is proposed, comprising the following steps:

[0016] The maleic anhydride copolymer and the PA resin are added into a twin-screw extruder, and the toughening masterbatch is prepared by mixing, melting, extruding and granulating; wherein the mass percentage of the maleic anhydride copolymer in the toughening masterbatch is 45-50%;

[0017] PA resin, toughening masterbatch, ethylene vinyl alcohol copolymer, inorganic filler, lubricant and antioxidant are mixed and added to the main feeding port of a twin-screw extruder, and melt-extruded and granulated in the twin-screw extruder to obtain a PA composite semi-finished product;

[0018] The PA composite semi-finished product and the chain extender are mixed and added to the main feeding port of a twin-screw extruder, and the mixture is melt-extruded and granulated in the twin-screw extruder to obtain the blow molding grade hydrogen storage tank liner material; wherein the weight percentage of each component in the blow molding grade hydrogen storage tank liner material is as follows: PA resin, 48-78%; toughening masterbatch, 20-50%; ethylene vinyl alcohol copolymer, 0.5-3%; inorganic filler, 0.5-3%; chain extender, 0.1-1%; lubricant, 0.4-0.8%; antioxidant, 0.2-0.5%.

[0019] Furthermore, the process parameters for blow molding of the blow molding grade hydrogen storage tank liner material are: the feeding section temperature is 240-245°C, the middle section temperature is 245-247°C, and the head temperature is 245-250°C.

[0020] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects:

[0021] The invention discloses a blow molding grade hydrogen storage tank liner material and a preparation method thereof. The material comprises the following components in weight percentage: PA resin, 48-78%; toughening masterbatch, 20-50%; ethylene vinyl alcohol copolymer, 0.5-3%; inorganic filler, 0.5-3%; chain extender, 0.1-1%; lubricant, 0.4-0.8%; antioxidant, 0.2-0.5%; wherein the toughening masterbatch is prepared by blending a maleic anhydride graft copolymer and a PA resin, and the mass percentage of the maleic anhydride graft copolymer is 45-50%; during the preparation, the maleic anhydride copolymer and the PA resin are firstly used to prepare the toughening masterbatch, and then the PA resin, the toughening masterbatch, the ethylene vinyl alcohol copolymer, the inorganic filler, the lubricant and The PA composite semi-finished product is mixed with an antioxidant, and finally the PA composite semi-finished product is mixed with a chain extender to obtain a blow molding grade hydrogen storage tank liner material; on the one hand, the present invention adopts a PA resin material with better hydrogen barrier property, and adds high barrier components, including EVOH high barrier polymer material and lamellar inorganic filler, to improve the hydrogen permeability of the nylon material, that is, to enhance the hydrogen barrier effect; on the other hand, the molecular weight and viscosity of the PA composite material are increased by viscosity enhancement with a chain extender and preparation of a toughening masterbatch so that the product can be formed by a blow molding process; the toughening masterbatch is added with a maleic anhydride graft copolymer to improve the low-temperature toughness and elongation at break of the material, thereby ensuring the toughness and ductility of the hydrogen storage tank liner under low temperature conditions.

[0022] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.

[0023] The foregoing and other aspects of the invention can be more fully understood from the following description in conjunction with the embodiments. Other additional aspects of the invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0025] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and similar words do not indicate a quantity limitation, but indicate the existence of at least one. "Include" or "comprises" and similar words mean that the elements or objects appearing before "include" or "comprises" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.

[0026] Based on the new standards for the storage safety requirements of hydrogen storage tanks, the polyamide modified materials proposed in the prior art can no longer meet the target high-pressure requirements of hydrogen storage tanks. When used under high-pressure conditions, the hydrogen permeability resistance of the existing PA6 modified materials decreases, and the product bubbling occurs. Therefore, it is necessary to develop new materials that can meet the standard requirements of hydrogen storage tanks to adapt to social development. The present invention proposes a blow molding grade hydrogen storage tank liner material and a preparation method thereof. The liner material is a PA modified material. The hydrogen barrier effect of the PA modified material is greatly improved through formula improvement and process improvement of the product.

[0027] Specifically, the blow molding grade hydrogen storage tank liner material disclosed in the present invention includes the following components in weight percentage: PA resin, 48-78%; toughening masterbatch, 20-50%; ethylene vinyl alcohol copolymer, 0.5-3%; inorganic filler, 0.5-3%; chain extender, 0.1-1%; lubricant, 0.4-0.8%; antioxidant, 0.2-0.5%; wherein the toughening masterbatch is prepared by blending a maleic anhydride grafted copolymer with a PA resin, the mass percentage of the maleic anhydride grafted copolymer in the toughening masterbatch is 45-50%, and the maleic anhydride grafted copolymer is at least one of maleic anhydride grafted POE, maleic anhydride grafted EPDM, and maleic anhydride grafted PE.

[0028] Optionally, the relative viscosity of the PA resin is not less than 2.5, and the PA resin is selected from one or more of PA6, PA610, PA612, PA11, PA12, PA1010, PA1012 and PA1212; the inorganic filler is a lamellar inorganic filler, and the lamellar inorganic filler is a combination of one or more of mica, wollastonite and montmorillonite; the amount of the chain extender does not exceed 2.5% of the total weight of the PA resin in the blow molding grade hydrogen storage tank liner material, and the chain extender is a linear molecular chain extender containing a polycarbonate functional group with a molecular weight of less than 20,000, for example, the chain extender is a PA6-carbonate polymer; the lubricant is a modified ethylene bis fatty acid amide; the antioxidant is one or more of antioxidant 168, antioxidant 1098, antioxidant 1010, and phosphite antioxidants;

[0029] During the preparation, maleic anhydride copolymer and PA resin are first added to a twin-screw extruder, and toughened masterbatch is obtained by mixing, melt extrusion and granulation; then, PA resin, toughened masterbatch, ethylene vinyl alcohol copolymer, inorganic filler, lubricant and antioxidant are mixed and added to the main feeding port of the twin-screw extruder, and melt extrusion and granulation are performed in the twin-screw extruder to obtain a PA composite material semi-finished product; subsequently, the PA composite material semi-finished product and chain extender are mixed and added to the main feeding port of the twin-screw extruder, and melt extrusion and granulation are performed in the twin-screw extruder to obtain the blow molding grade hydrogen storage tank liner material.

[0030] When the blow molding grade hydrogen storage tank liner material is blow molded into an liner product, the following process parameters are selected: the feeding section temperature is 240-245°C, the middle section temperature is 245-247°C, and the die head temperature is 245-250°C.

[0031] The blow molding grade hydrogen storage tank liner material and the preparation method thereof disclosed in the present invention are further described in detail below in conjunction with specific embodiments. The sources of the reagents in the embodiments are as follows:

[0032] PA6: relative viscosity 3.8, BASF;

[0033] PA610: relative viscosity 2.5, wide range;

[0034] PA612: relative viscosity 2.5, wide range;

[0035] PA1012: relative viscosity 2.5, Dongchen;

[0036] Maleic anhydride grafted ethylene-octene copolymer (mPOE), purchased from DOW, brand Fusabond N493;

[0037] Maleic anhydride grafted EPDM, purchased from DOW, brand Fusabond N416;

[0038] Maleic anhydride grafted PE was purchased from Nanhai Bochen with the brand name AD-88.

[0039] Example 1

[0040] The maleic anhydride copolymer and the PA resin are added into a twin-screw extruder, and the mixture is mixed, melt-extruded and granulated to obtain a toughening masterbatch; wherein the mass percentage of the maleic anhydride copolymer in the toughening masterbatch is 50%; the PA resin, the toughening masterbatch, the ethylene vinyl alcohol copolymer, the inorganic filler, the lubricant and the antioxidant are mixed and added to the main feeding port of the twin-screw extruder, and the semi-finished PA composite material is obtained by melt-extrusion granulation in the twin-screw extruder; the semi-finished PA composite material and the chain extender are mixed and added to the main feeding port of the twin-screw extruder, and the mixture is melt-extruded and granulated to obtain a semi-finished PA composite material; The blow molding grade hydrogen storage tank liner material is obtained by melt extrusion granulation in a twin-screw extruder; wherein the weight percentage of each component in the blow molding grade hydrogen storage tank liner material is as follows: PA resin, 65%; toughening masterbatch, 32%; ethylene vinyl alcohol copolymer, i.e. EVOH high barrier polymer material, 1.2%; inorganic filler selected flaky mica, 1.0%; chain extender selected PA6-carbonate polymer, 0.2%; lubricant selected modified ethylene bis fatty acid amide, 0.4%; antioxidant selected antioxidant 1098, 0.2%.

[0041] In the above scheme, the PA resin and the PA resin in the toughening masterbatch are obtained by mixing PA6 and PA1012 in a mass ratio of 5:3, and the maleic anhydride grafted copolymer in the toughening masterbatch is obtained by mixing maleic anhydride grafted POE and maleic anhydride grafted PE in a mass ratio of 3:2.

[0042] Example 2

[0043] The maleic anhydride copolymer, PA resin, dispersant and heat stabilizer are added to a twin-screw extruder, and the mixture is melt-extruded and granulated to obtain a toughening masterbatch; wherein the mass percentage of the maleic anhydride copolymer in the toughening masterbatch is 50%; the PA resin, toughening masterbatch, ethylene vinyl alcohol copolymer, inorganic filler, lubricant and antioxidant are mixed and added to the main feeding port of the twin-screw extruder, and the semi-finished PA composite material is obtained by melt-extrusion granulation in the twin-screw extruder; the semi-finished PA composite material and chain extender are mixed and added to the main feeding port of the twin-screw extruder. The material is melt-extruded and granulated in a twin-screw extruder to obtain the blow molding grade hydrogen storage tank liner material; wherein the weight percentage of each component in the blow molding grade hydrogen storage tank liner material is as follows: PA resin, 65%; toughening masterbatch, 32%; ethylene vinyl alcohol copolymer, i.e. EVOH high barrier polymer material, 1.2%; inorganic filler selected flaky mica, 1.0%; chain extender selected PA6-carbonate polymer, 0.2%; lubricant selected modified ethylene bis fatty acid amide, 0.4%; antioxidant selected antioxidant 1098, 0.2%.

[0044] In the above scheme, the PA resin and the PA resin in the toughening masterbatch are obtained by mixing PA6 and PA610 in a mass ratio of 5:3, and the maleic anhydride grafted copolymer in the toughening masterbatch is obtained by mixing maleic anhydride grafted POE and maleic anhydride grafted PE in a mass ratio of 3:2.

[0045] Example 3

[0046] The maleic anhydride copolymer, PA resin, dispersant and heat stabilizer are added to a twin-screw extruder, and the mixture is melt-extruded and granulated to obtain a toughening masterbatch; wherein the mass percentage of the maleic anhydride copolymer in the toughening masterbatch is 50%; the PA resin, toughening masterbatch, ethylene vinyl alcohol copolymer, inorganic filler, lubricant and antioxidant are mixed and added to the main feeding port of the twin-screw extruder, and the mixture is melt-extruded and granulated in the twin-screw extruder to obtain a PA composite semi-finished product; the PA composite semi-finished product and chain extender are mixed and added to the main feeding port of the twin-screw extruder; The main feeding port is used for melt extrusion and granulation in a twin-screw extruder to obtain the blow molding grade hydrogen storage tank liner material; wherein the weight percentage of each component in the blow molding grade hydrogen storage tank liner material is as follows: PA resin, 52%; toughening masterbatch, 40%; ethylene vinyl alcohol copolymer, i.e. EVOH high barrier polymer material, 3%; inorganic filler selected as flaky mica, 3%; chain extender selected as PA6-carbonate polymer, 1.0%; lubricant selected as modified ethylene bis fatty acid amide, 0.6%; antioxidant selected as antioxidant 1098, 0.4%.

[0047] In the above scheme, the PA resin and the PA resin in the toughening masterbatch are obtained by mixing PA612 and PA1012 in a mass ratio of 1:1, and the maleic anhydride grafted copolymer in the toughening masterbatch is obtained by mixing maleic anhydride grafted EPDM and maleic anhydride grafted POE in a mass ratio of 3:2.

[0048] The difference between Examples 4-10 and Comparative Examples 1-4 and Example 3 is that the components and component ratios in the blow molding grade hydrogen storage tank liner material are different, including the composition of the PA resin, the composition of the toughening masterbatch, and the addition ratio of each component, as shown in Table 1 below.

[0049] Table 1 Composition ratio of materials made of Examples 1-10 and Comparative Examples 1-4

[0050]

[0051]

[0052] The blow molding grade hydrogen storage tank liner materials prepared in Examples 1-10 and Comparative Examples 1-4 were used for hydrogen permeability, tensile strength and impact resistance tests. The test results are shown in Table 2 below.

[0053] Table 2 Performance data of materials made from Examples 1-10 and Comparative Examples 1-4

[0054]

[0055] In Examples 1-10 and Comparative Examples 1-4, the performance testing method of the prepared hydrogen storage tank liner material is as follows:

[0056] The hydrogen permeability of the material was tested with reference to the standard GB / T 42610, the tensile strength of the material was tested with reference to the standard ISO527-2012, and the impact strength of the material was tested with reference to the standard ISO 179-2010. The test data fully show that the use of PA resin materials with better hydrogen barrier properties, combined with the addition of high barrier components, including EVOH high barrier polymer materials, lamellar inorganic fillers, such as Example 10, Examples 3-5 and Comparative Examples 1 and 4, can indeed effectively improve the hydrogen permeability of nylon materials; by adjusting the composition ratio and addition amount of each component, the hydrogen barrier effect can be effectively improved; combined with the test results of Examples 3, 7-10, and Comparative Example 1, it is shown that the chain extender viscosity enhancement and the preparation of toughening masterbatch to increase the molecular weight and viscosity of the PA composite material can not only enable the material to be formed into products using the blow molding process, but also help improve the hydrogen barrier effect while improving the impact toughness of the material, thereby ensuring the toughness and ductility of the hydrogen storage tank liner under low temperature conditions, and obtaining a product that meets the current hydrogen storage tank storage standards.

[0057] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A blow molding grade hydrogen storage tank liner material, characterized in that: The composition comprises the following components in weight percentage: PA resin, 48-78%; Toughening masterbatch, 20-50% Ethylene vinyl alcohol copolymer, 0.5-3%; Inorganic filler, 0.5-3%; Chain extender, 0.1-1%; Lubricant, 0.4-0.8%; Antioxidant, 0.2-0.5%.

2. The blow molding grade hydrogen storage tank liner material according to claim 1, characterized in that: The toughening masterbatch is prepared by blending a maleic anhydride graft copolymer and a PA resin, wherein the mass percentage of the maleic anhydride graft copolymer is 45-50%.

3. The blow molding grade hydrogen storage tank liner material according to claim 1, characterized in that: The PA resin is selected from one or more of PA6, PA610, PA612, PA11, PA12, PA1010, PA1012 and PA1212.

4. The blow molding grade hydrogen storage tank liner material according to claim 1 or 2, characterized in that: The relative viscosity of the PA resin is not less than 2.

5.

5. The blow molding grade hydrogen storage tank liner material according to claim 1, characterized in that: The inorganic filler is a lamellar inorganic filler, and the lamellar inorganic filler is one or more combinations of mica, wollastonite and montmorillonite.

6. The blow molding grade hydrogen storage tank liner material according to claim 2, characterized in that: The maleic anhydride grafted copolymer is at least one of maleic anhydride grafted POE, maleic anhydride grafted EPDM, and maleic anhydride grafted PE.

7. The blow molding grade hydrogen storage tank liner material according to claim 1, characterized in that: The amount of the chain extender does not exceed 2.5% of the total weight of the PA resin in the blow molding grade hydrogen storage tank liner material, and the chain extender is a linear molecular chain extender containing polycarbonate functional groups with a molecular weight less than 20,000.

8. The blow molding grade hydrogen storage tank liner material according to claim 1, characterized in that: The chain extender is a linear molecular chain extender containing a polycarbonate functional group.

9. A method for preparing a blow molding grade hydrogen storage tank liner material, characterized in that: The steps include: The maleic anhydride copolymer and the PA resin are added into a twin-screw extruder, and the toughening masterbatch is prepared by mixing, melting, extruding and granulating; wherein the mass percentage of the maleic anhydride copolymer in the toughening masterbatch is 45-50%; PA resin, toughening masterbatch, ethylene vinyl alcohol copolymer, inorganic filler, lubricant and antioxidant are mixed and added to the main feeding port of a twin-screw extruder, and melt-extruded and granulated in the twin-screw extruder to obtain a PA composite semi-finished product; The PA composite semi-finished product and the chain extender are mixed and added to the main feeding port of a twin-screw extruder, and the mixture is melt-extruded and granulated in the twin-screw extruder to obtain the blow molding grade hydrogen storage tank liner material; wherein the weight percentage of each component in the blow molding grade hydrogen storage tank liner material is as follows: PA resin, 48-78%; toughening masterbatch, 20-50%; ethylene vinyl alcohol copolymer, 0.5-3%; inorganic filler, 0.5-3%; chain extender, 0.1-1%; lubricant, 0.4-0.8%; antioxidant, 0.2-0.5%.

10. The method for preparing the blow molding grade hydrogen storage tank liner material according to claim 9, characterized in that: The process parameters for blow molding of the blow-molding-grade hydrogen storage tank liner material are as follows: the feeding section temperature is 240-245°C, the middle section temperature is 245-247°C, and the die head temperature is 245-250°C.

Citation Information

Patent Citations

  • Polyamide resin composition for hydrogen gas storage containers or hydrogen gas preparation pipes

    CN110511560A

  • Composition for inner container of gas storage tank as well as preparation method and application of composition

    CN117624879A

Cited By

  • Composite material with high gas barrier property, preparation method and blood culture bottle

    CN120269908A

  • Low-temperature high-ductility nylon material for hydrogen storage tank liner

    CN120966240A